Characterization of ∑-Semicompleteness via Caristi's Fixed Point Theorem in Semimetric Spaces. (1st March 2018) - Suzuki, Tomonari
Abstract : Introducing the concept of∑ -semicompleteness in semimetric spaces, we extend Caristi's fixed point theorem to∑ -semicomplete semimetric spaces. Via this extension, we characterize∑ -semicompleteness. We also give generalizations of the Banach contraction principle.